2013
DOI: 10.3945/ajcn.112.056333
|View full text |Cite
|
Sign up to set email alerts
|

Adapted dietary inflammatory index and its association with a summary score for low-grade inflammation and markers of glucose metabolism: the Cohort study on Diabetes and Atherosclerosis Maastricht (CODAM) and the Hoorn study

Abstract: The significant mediating role of low-grade inflammation in the association between the ADII and HOMA-IR suggests that inflammation might be one of the pathways through which diet affects insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
165
2
25

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(204 citation statements)
references
References 35 publications
12
165
2
25
Order By: Relevance
“…Previously, we observed that women with a pro-inflammatory diet (higher DII scores) had a higher risk of developing CRC in a US-based cohort study (Shivappa et al 2014a). Furthermore, higher DII scores have been linked to asthma (Wood et al 2014), and using a modification of the previous DII version (Hebert et al 2014), a positive association was observed between the DII and higher concentrations of glucose metabolism markers (van Woudenbergh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we observed that women with a pro-inflammatory diet (higher DII scores) had a higher risk of developing CRC in a US-based cohort study (Shivappa et al 2014a). Furthermore, higher DII scores have been linked to asthma (Wood et al 2014), and using a modification of the previous DII version (Hebert et al 2014), a positive association was observed between the DII and higher concentrations of glucose metabolism markers (van Woudenbergh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain a robust measure of overall inflammation and endothelial dysfunction we computed composite scores as described before (30,32,33). With these composite scores we reduce biological variability and random error of each individual variable, and we gain statistical efficiency.…”
Section: Statistical Analysis and Study Powermentioning
confidence: 99%
“…In CODAM, IL6, SAA, sICAM1, sE-selectin, and sVCAM1 were also measured by ELISA and CRP was also measured in serum by high-sensitivity immunoturbidimetry (31). Values obtained by ELISA or immunoturbidimetry assay were calibrated on the values obtained by multi-array and the calibrated and multi-array values were averaged for CODAM (30). von Willebrand factor (vWF) was determined in citrated plasma by means of ELISA (29).…”
Section: Markers Of Low-grade Inflammation and Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waist circumference was ascertained with a measuring tape at the level of umbilicus. Blood samples were drawn after an overnight fast for measurement of glycated hemoglobin (HbA 1c ), plasma glucose, insulin, total cholesterol, HDL cholesterol, and triglycerides, as described elsewhere (24,25). LDL cholesterol was calculated by the Friedewald formula.…”
Section: Measurementsmentioning
confidence: 99%